2022
DOI: 10.1016/j.prosdent.2020.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Determining of canine position by multiple facial landmarks to achieve natural esthetics in complete denture treatment

Abstract: Patients who have lost their teeth experience not only compromised mastication and pronunciation but also the emotional damage of losing their natural physical appearance. 1 Thus, the goal of a complete denture includes helping the patient to regain confidence in their appearance. This requires knowledge and understanding of both the physical and biologic factors. 2 The best way to select artificial teeth is from preextraction records, including diagnostic casts, radiographs, and recent images showing a natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Furthermore, this study found that the value of facial dimensions and ICaD were significantly larger in men than in women, consistent with the findings of most previous studies [ 11 , [32] , [33] , [34] , [35] ], which indicated that men and women should be analyzed separately for dentofacial relationships. However, no sex differences in IPD were observed respectively in the studies of Freihofer HP [ 36 ] and Gomes [ 9 ], which may be attributed to differences in race or measuring methods.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, this study found that the value of facial dimensions and ICaD were significantly larger in men than in women, consistent with the findings of most previous studies [ 11 , [32] , [33] , [34] , [35] ], which indicated that men and women should be analyzed separately for dentofacial relationships. However, no sex differences in IPD were observed respectively in the studies of Freihofer HP [ 36 ] and Gomes [ 9 ], which may be attributed to differences in race or measuring methods.…”
Section: Discussionsupporting
confidence: 91%
“…When choosing artificial anterior teeth width according to a tooth mold chart, the distance between the distal contact points of the canines is used, rather than the distance between the canine cusps [ 10 ]. Therefore, the ideal reference landmark in the clinic for tooth selection is the distal surface of the canine rather than the cusp tip [ 11 ]. A few facial anthropometric measurements have been suggested to assist in determining the width of artificial maxillary anterior teeth in patients with edentulism.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations